2016
DOI: 10.2220/biomedres.37.199
|View full text |Cite
|
Sign up to set email alerts
|

<b>Vitamin D</b><b><sub>3</sub></b><b> analog maxacalcitol (OCT) induces hCAP-18/LL-37 production in human oral epithelial </b><b>cells </b>

Abstract: Maxacalcitol (22-oxacalcitriol: OCT) is a synthetic vitamin D 3 analog with a limited calcemic effect. In this study, we investigated whether OCT increases the production of LL-37/CAP-18, a human cathelicidin antimicrobial peptide, in human gingival/oral epithelial cells. A human gingival epithelial cell line (Ca9-22) and human oral epithelial cell lines (HSC-2, HSC-3, and HSC-4) exhibited the enhanced expression of LL-37 mRNA upon stimulation with OCT as well as active metabolites of vitamins D 3 and D 2 . Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 28 publications
0
13
2
Order By: Relevance
“…In the study by Tada et al., a human gingival epithelial cell line (Ca9‐22) exhibited increased expression of hCAP‐18/LL‐37 upon stimulation with either 100 nM 1,25‐(OH)VD analog or 100 nM 1,25‐(OH)VD. The enhancement was as much as 75‐fold compared with that of the negative control in 24 hours and even higher with longer incubation time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Tada et al., a human gingival epithelial cell line (Ca9‐22) exhibited increased expression of hCAP‐18/LL‐37 upon stimulation with either 100 nM 1,25‐(OH)VD analog or 100 nM 1,25‐(OH)VD. The enhancement was as much as 75‐fold compared with that of the negative control in 24 hours and even higher with longer incubation time.…”
Section: Discussionmentioning
confidence: 99%
“…hCAP‐18/LL‐37 has also been detected in human gingival crevicular fluids (GCF), with patients with aggressive or chronic periodontitis exhibiting higher LL‐37 levels in GCF than controls . In in vitro studies, stimulation of gingival/oral epithelial cells using 25‐(OH)VD, 1,25‐(OH)VD, or its analog resulted in an elevation of hCAP‐18/LL‐37 expression . The question was raised whether the vitamin D induction of hCAP‐18/LL‐37 may also exist in periodontal soft tissue cells such as hGFs and hPDLCs.…”
mentioning
confidence: 99%
“…We reported previously that P. gingivalis infection increases IL-33 production in human gingival epithelial cells in a gingipain-dependent manner (30). OCT induces the production of hCAP-18 protein, but not LL-37 protein by human gingival epithelial cells (31). We showed that OCT-induced hCAP-18/ LL-37 production was attenuated by the infection with P. gingivalis ATCC 33277, but not a gingipain-null P. gingivalis mutant KDP136.…”
Section: Discussionmentioning
confidence: 57%
“…1A). We reported previously that Ca9-22 cells produce the precursor hCAP-18, but not LL-37, induced by OCT (31). Then, we examined whether P. gingivalis infection induces hCAP-18 production by Ca9-22 cells.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation